(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص: يهدف هذا البحث إلى تسليط الضوء على المسؤولية الجزائية للمنشآت الصناعية والجرائم التي ترتكب في الساحل، فموضوع جريمة تلوث الساحل والمسؤولية الناجمة عنها من الموضوعات الحديثة في مجال الدراسات القانونية- وخاصة المجال الجنائي منها- وأمام الضغوطات المختلفة على الساحل كإقليم لتواجد البشر والنشاطات، بات من الضروري تدخل المشرع الجزائري إلى سن قوانين تنظيمية ومراسيم تشريعية لحماية الساحل وتثمينه، حيث أنّ التدخل القبلي لتوفير الحماية مسبقا وتفعيل مجال التوعية أمران هامان لإنجاح الحماية الجنائية للساحل. فالأمر يتعلق بتحديد المسؤول عن الجريمة المرتكبة بقدر ما هو ضرورة للحفاظ على عناصر البيئة بصفة عامة والساحل على وجه الخصوص. كلمات دالة : المسؤولية الجنائية ، الساحل ، المنشآت الصناعية ، الحماية الجزائية ، الجريمة البيئية Abstract : This research aims to highlight the penal liability of industrial enterprises and offences committed on the coast The offence of coastal pollution and the liability arising there from recent topics in the field of legal studies - in particular the criminal field thereof - and in the face of various pressures on the coast as a territory for the presence of human beings and activities, The Algerian legislature’s intervention in the enactment of regulatory acts and legislative decrees to protect and value the Sahel s criminal protection ", since pre-protection tribal intervention and effective outreach were important to the success of the criminal protection of the coast. It was as much about who was responsible for the crime as it was necessary to preserve the elements of the environment in general and the coast in particular. Key words: criminal liability , coastline , industrial installations , Algerian protection , environmental crime